The analysis of gut microbiota in patients with bile acid diarrhoea treated with colesevelam - Kumar, Aditi; Quraishi, Mohammed Nabil; Al-Hassi, Hafid O.; El-Asrag, Mohammed E.; Segal, Jonathan P.; Jain, Manushri; Steed, Helen; Butterworth, Jeffrey; Farmer, Adam; Mclaughlin, John; Beggs, Andrew; Brookes, Matthew J. (Frontiers in Microbiology, 2023)
Introduction Bile acid diarrhoea (BAD) is a common disorder that results from an increased loss of primary bile acids and can result in a change in microbiome. The aims of this study were to characterise the microbiome in different cohorts of patients with BAD and to determine if treatment with a bile acid sequestrant, colesevelam, can alter the microbiome and improve microbial diversity. Materials and methods Patients with symptoms of diarrhoea underwent 75-selenium homocholic acid (75SeHCAT) testing and were categorised into four cohorts: idiopathic BAD, post-cholecystectomy BAD, post-operative Crohn’s disease BAD and 75SeHCAT negative control group. Patients with a positive 75SeHCAT (<15%) were given a trial of treatment with colesevelam. Stool samples were collected pre-treatment, 4-weeks, 8-weeks and 6–12 months post-treatment. Faecal 16S ribosomal RNA gene analysis was undertaken. Results A total of 257 samples were analysed from 134 patients. α-diversity was significantly reduced in patients with BAD and more specifically, in the idiopathic BAD cohort and in patients with severe disease (SeHCAT <5%); p < 0.05. Colesevelam did not alter bacterial α/β-diversity but patients who clinically responded to treatment had a significantly greater abundance of Fusobacteria and Ruminococcus, both of which aid in the conversion of primary to secondary bile acids. Conclusion This is the first study to examine treatment effects on the microbiome in BAD, which demonstrated a possible association with colesevelam on the microbiome through bile acid modulation in clinical responders. Larger studies are now needed to establish a causal relationship with colesevelam and the inter-crosstalk between bile acids and the microbiome.